2021
DOI: 10.1186/s40463-021-00545-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of endolymphatic duct blockage, endolymphatic sac drainage and endolymphatic sac decompression surgery in reversing endolymphatic hydrops in Meniere's disease

Abstract: Background To explore the differences between endolymphatic duct blockage, endolymphatic sac drainage and endolymphatic sac decompression surgery in the reversal of endolymphatic hydrops (EH) in patients with intractable Meniere’s disease (MD). Methods A total of 27 MD patients receiving endolymphatic duct blockage surgery (n = 10), endolymphatic sac drainage surgery (n = 9) and endolymphatic sac decompression surgery (n = 8) underwent gadolinium-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Based on the fact that the intact iES epithelium is as same as that of control cases in the patients with degenerative and hypoplastic eES pathology, 16 the ES drainage surgery, by incising the ES lumen from the eES to the distal iES, may be an alternative treatment option for releasing the surplus of endolymph in the inner ear in these patients. The result in our previous study has shown the EH in these MD patients with atrophic eES also could be reversed following this modified ES drainage surgery 36 . Therefore, based on the different pathogenesis of the production of EH, a personalized treatment should be considered in these two subgroups of MD patients with normoplastic eES and atrophic eES.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on the fact that the intact iES epithelium is as same as that of control cases in the patients with degenerative and hypoplastic eES pathology, 16 the ES drainage surgery, by incising the ES lumen from the eES to the distal iES, may be an alternative treatment option for releasing the surplus of endolymph in the inner ear in these patients. The result in our previous study has shown the EH in these MD patients with atrophic eES also could be reversed following this modified ES drainage surgery 36 . Therefore, based on the different pathogenesis of the production of EH, a personalized treatment should be considered in these two subgroups of MD patients with normoplastic eES and atrophic eES.…”
Section: Discussionmentioning
confidence: 92%
“…The result in our previous study has shown the EH in these MD patients with atrophic eES also could be reversed following this modified ES drainage surgery. 36 Therefore, based on the different pathogenesis of the production of EH, a personalized treatment should be considered in these two subgroups of MD patients with normoplastic eES and atrophic eES. Figure 7 lays out a working drawing for EDB surgery on patients with normoplastic eES and ES drainage surgery on patients with atrophic eES.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the fact that the operation alleviates the rapid expansion of membranous labyrinthine hydrops rather than cures it. Notably, the membranous labyrinthine hydrops caused by vascular risk factors or other causes persists after surgery ( 30 ). The operation just prevents further aggravation of the condition owing to arteriovenous mixing, which may result from endolymphatic sac vessel reflux to the inner ear due to excessive pressure ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Paparella ( 29 ) proposed that endolymphatic sac surgery is likely to enhance the blood supply of the sac and improves its absorption function such that alleviates endolymphatic hydrops. A recent study compared the changes of endolymphatic hydrops after different surgeries through enhanced MRI ( 30 ). The results showed that endolymphatic hydrops was improved in some patients after ESMS and endolymphatic duct blockage surgery but not in those patients with ESD surgery ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared the changes of endolymphatic hydrops after different surgeries through enhanced MRI ( 30 ). The results showed that endolymphatic hydrops was improved in some patients after ESMS and endolymphatic duct blockage surgery but not in those patients with ESD surgery ( 30 ). Taking all these into account, therefore, we suggest that the possible reasons for the better outcome of WESD for intractable MD are as follows: ( 1 ) extensive decompression of the endolymphatic sac and dura is supposed to reduce the local impact of granulation tissue, fibrous tissue proliferation, and new bone formation on the endolymphatic sac after surgery; ( 2 ) the local hydrostatic pressure and osmotic pressure are changed; ( 3 ) extensive decompression affects the blood supply of the endolymphatic sac, resulting in the alteration of the endolymphatic sac activity; and ( 4 ) reduced secretion of glycoprotein, in turn, reduced endolymph influx to the endolymphatic sac such that relieve an attack of vertigo.…”
Section: Discussionmentioning
confidence: 99%